Role of Dietary Long-Chain Polyunsaturated Fatty Acids in Infant Allergies and Respiratory Diseases - Lynette P. Shek; Mary Foong-Fong Chong; Jia Yi Lim; Shu-E Soh; Yap-Seng Chong (Clinical and Developmental Immunology)
Maternal nutrition has critical effects on the developing structures and functions of the fetus. Malnutrition during pregnancy can result in low birth weight and small for gestational age babies, increase risk for infection, and impact the immune system. Long-chain polyunsaturated fatty acids (PUFAs) have been reported to have immunomodulatory effects. Decreased consumption of omega-6 PUFAs, in favor of more anti-inflammatory omega-3 PUFAs in modern diets, has demonstrated the potential protective role of omega-3 PUFAs in allergic and respiratory diseases. In this paper, we examine the role of PUFAs consumption during pregnancy and early childhood and its influence on allergy and respiratory diseases. PUFAs act via several mechanisms to modulate immune function. Omega-3 PUFAs may alter the T helper (Th) cell balance by inhibiting cytokine production which in turn inhibits immunoglobulin E synthesis and Th type 2 cell differentiation. PUFAs may further modify cellular membrane, induce eicosanoid metabolism, and alter gene expression. These studies indicate the benefits of omega-3 PUFAs supplementation. Nevertheless, further investigations are warranted to assess the long-term effects of omega-3 PUFAs in preventing other immune-mediated diseases, as well as its effects on the later immunodefense and health status during early growth and development.